Management of Hepatic Rupture Diagnosed after an Emergency Cesarean Section - Gianluca Raffaello Damiani; Viviana Merola; Mario Barnaba; Stefano Landi; Gennaro Cormio; Antonio Pellegrino (Case Reports in Medicine)
A careful management of hepatic capsular rupture, with massive hemoperitoneum which occurred 14 hours after an emergency cesarean section at 36 weeks of gestation, is meticulously reported. The grade of hepatic involvement varies from minor capsular laceration to extensive parenchymal rupture. Our management involved a combination of surgical interventions and aggressive supportive care. The patient was discharged after 53 days and 4 laparotomies and an unsuccessful attempt of superselective artery embolization. Ultrasound after 40 days from the last surgery showed uniform hepatic parenchyma free of focal lesions. Due to the rarity and the unpredictability nature of this devastating event we believe necessary to report our experience, reinforcing the importance of the postsurgery management.